Investigation of the Cape Fear arch and East Coast fault system in the Coastal Plain of North Carolina and northeastern South Carolina, USA, using LiDAR data - Marple, Ronald T.; Hurd, James D. (Atlantic Geology, 2021)
LiDAR data collected in the Coastal Plain of the Carolinas revealed numerous, mostly NW-SE-oriented lineaments that cross the Cape Fear arch, the longest of which are the 50- to 115-km-long, NW-SE-oriented Faison, Jarmantown, Livingston Creek, and White Marsh lineaments and the ~50-km-long, ENE-WSW-oriented Tomahawk lineament in southeastern North Carolina. Their interpretation is based mainly on locally incised channels, abrupt stream bends, topographic scarps, and linear areas of uplifted Coastal Plain sediments. The Precambrian to Paleozoic Graingers basin or synform in the pre-Cretaceous basement terminates to the southwest along the ~28-km-long, 3- to 7-km-wide Jarmantown high. The ~115-km-long Jarmantown lineament may be the surface expression of the previously reported Neuse fault, the location of which has been controversial. The Jarmantown and other lineaments crossing the Cape Fear arch suggest that the arch is structurally complex. Further investigation of the East Coast fault system (ECFS) along the west side of the Cape Fear arch in North Carolina revealed that it is located farther to the northwest than previously reported, thereby making it continuous with the ECFS in northeastern South Carolina where it forms a ~15° restraining bend. We postulate that the interpreted faults crossing the Cape Fear arch in southeastern North Carolina formed to compensate for the increased compression and change in volume from dextral motion along the fault bend. Holocene paleoliquefaction deposits near the coast, a vertically offset Pleistocene(?) beach ridge along the interpreted Faison fault, and Tertiary surface faults along the ECFS northeast of Smithfield, North Carolina, suggest that large Quaternary earthquakes may have occurred along the ECFS, the Faison and Neuse faults, and other interpreted faults that cross the Cape Fear arch.